SIMULATION TO ENHANCE PERFORMANCE OF GLOBE VALVE - Mohd Nuri Al-Amin, Nu’man Al-Basyir (IRC, 2021)
Globe valves serve many purposes in oil and gas facilities as a tool to control fluid flow in pipelines.